2022
DOI: 10.1021/acscatal.1c05509
|View full text |Cite
|
Sign up to set email alerts
|

Role of High-Spin Species and Pendant Amines in Electrocatalytic Alcohol Oxidation by a Nickel Phosphine Complex

Abstract: The development of active and efficient electrocatalysts for oxidation of alcohols using earth-abundant metals will aid progress toward a renewable energy economy. Here, we present a detailed mechanistic study of electrocatalytic benzyl alcohol oxidation by a molecular nickel complex containing pendant amines using a combination of kinetic studies, nuclear magnetic resonance spectroscopy, and density functional theory. The catalyst preferentially binds alcohol in a high-spin octahedral geometry, but this comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…261 The mechanism for oxidation of benzyl alcohol was investigated experimentally and computationally, and the proposed catalytic cycle is shown in Figure 57. 262 Similar to the case with formate oxidation, the pendant amine is proposed to facilitate oxidation of the metal hydride complex at a mild potential. The rate of catalysis was found to be limited by alcohol binding and subsequent deprotonation by exogenous base to afford a nickel alkoxide intermediate.…”
Section: Electrocatalytic Oxidation Of Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…261 The mechanism for oxidation of benzyl alcohol was investigated experimentally and computationally, and the proposed catalytic cycle is shown in Figure 57. 262 Similar to the case with formate oxidation, the pendant amine is proposed to facilitate oxidation of the metal hydride complex at a mild potential. The rate of catalysis was found to be limited by alcohol binding and subsequent deprotonation by exogenous base to afford a nickel alkoxide intermediate.…”
Section: Electrocatalytic Oxidation Of Alcoholsmentioning
confidence: 99%
“…The mechanism for oxidation of benzyl alcohol was investigated experimentally and computationally, and the proposed catalytic cycle is shown in Figure . Similar to the case with formate oxidation, the pendant amine is proposed to facilitate oxidation of the metal hydride complex at a mild potential.…”
Section: Catalytic Reactions Beyond H2mentioning
confidence: 99%
“…Under the buffered conditions described above, [Ni(P tBu 2 N tBu 2 )(MeCN) 2 ] 2+ catalyzes the oxidation of BnOH at E cat/2 = −0.71 V vs Fc +/0 , corresponding to an overpotential of 0.39 V. As shown in Figure 6, the catalytic cycle is proposed to involve generation of an alkoxide complex as the rate-limiting step. 21 This species undergoes -hydride elimination to release benzaldehyde. Oxidation of the resulting Ni(II) hydride, which is the potential determining step, occurs at a mild potential because of the presence of the pendant amine, which provides a pathway for intramolecular proton transfer.…”
Section: Evaluation Of Overpotential For Known Electrocatalysts For O...mentioning
confidence: 99%
“…6, the catalytic cycle is proposed to involve generation of an alkoxide complex as the rate-limiting step. 21 This species undergoes β-hydride elimination to release benzaldehyde. Oxidation of the resulting Ni( ii ) hydride, which is the potential determining step, occurs at a mild potential because of the presence of the pendant amine, which provides a pathway for intramolecular proton transfer.…”
Section: Introductionmentioning
confidence: 99%
“…For example nickel-alkoxides are demonstrated to be intermediates in coupling processes (via ligand exchange or β-H abstraction, Scheme 3, top). [23,[41][42][43][44][45][46] Furthermore, insertion in NiÀ O bonds of CO 2 , CO, nitriles, ketones, isocyanate (Scheme 3, bottom); [35,36,38,39] has been established for neutral mono-alkoxide nickel complexes; as well as [OR] À ligand exchange [33] and formal reductive elimination at Ni. [37] During these studies, and as mentioned by Krossing et al, we observed that PhF!Al(OR F ) 3 adduct suffers from poor thermal stability liberating the Al(OR F ) 3 Lewis acid at room temperature, that evolves via abstraction of one of its own fluorine to form the [(R F O) 2 Al(μ-F)] 3 ring 2 (see below, Scheme 4).…”
Section: Introductionmentioning
confidence: 99%